2008
DOI: 10.1016/j.jcrs.2008.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Transmittance characteristics of ultraviolet and blue-light-filtering intraocular lenses

Abstract: The absorption characteristics of some UV and blue-light-filtering IOLs resembled those of the crystalline lens, but some differed. Long-term clinical trials should be performed to determine how blue-blocking IOLs affect the risk for progression of age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 27 publications
3
48
0
2
Order By: Relevance
“…The spectral transmittance values of the Alcon clear and/or yellow-tinted IOLs, the Hoya clear and/or yellowtinted IOLs, and the Kowa yellow-tinted IOLs have been reported previously [11,[15][16][17][18][19]. To the best of our knowledge, no transmission characteristics of the IOLs identified in the current study (Fig.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…The spectral transmittance values of the Alcon clear and/or yellow-tinted IOLs, the Hoya clear and/or yellowtinted IOLs, and the Kowa yellow-tinted IOLs have been reported previously [11,[15][16][17][18][19]. To the best of our knowledge, no transmission characteristics of the IOLs identified in the current study (Fig.…”
Section: Discussionsupporting
confidence: 43%
“…To estimate the hazards of sunlight to the retina, the BLI values and t max values were calculated for both aphakic and phakic eyes based on the guidelines provided by the American Conference of Industrial Hygienists [22,23] and by the International Commission on Non-Ionizing Radiation Protection [18], and for pseudophakic eyes using the percent transmittance data for the IOLs obtained in the current study (Table 1). All IOLs tested had smaller BLI values and longer t max values compared to those for aphakic eyes (15.00 mW/cm 2 and 0.67 s, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 However, previous studies mainly focused on yellow-tinted blue light-filtering IOLs, such as the Acrysof SN60AT Natural (Alcon Laboratories, Inc.) and the Hoya AF-1(UY) YA-60BB (Hoya Surgical Optics, Inc.); the studies found that the transmission rates were slightly higher than that of a middle-aged human lens (approximately 5% at 400 nm and 70% at 500 nm). [43][44][45][46] In contrast, we evaluated an orange-tinted blue light-filtering IOL, the PC 440 Y Orange Series IOL, which is characterized by more powerful spectral absorption properties than a human lens, and compared the results with those of a conventional clear UV lightfiltering IOL, the PC 430 Elite Series IOL. [14][15][16][17][18][19][44][45][46] We evaluated the scotopic and photopic visual acuity, contrast sensitivity, color discrimination, and potential postoperative visual symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the specific color of the chromophore, the Orange Series IOL is supposed to mimic more closely the protective physiologic properties of a middleaged human lens (approximately 60 years of age), resulting in less chromatic aberration and glare disability and an overall improvement in visual performance. 43 Laboratory studies measuring transmittance characteristics [43][44][45][46] showed that this IOL has excellent light-attenuation properties with absorption rates of approximately 90% at 427 nm and 43% at 500 nm, being even more powerful than commonly available blue light-filtering IOLs. This might be of interest because blue-light hazard peaks at approximately 430 nm.…”
mentioning
confidence: 99%